Novel Urinary Biomarkers for Diagnosis of Acute Pyelonephritis in Children (Iranian Journal of Kidney Diseases, 2020)
Urinary tract infection (UTI) is common among pediatric population. Pyelonephritis, especially in young infants, is associated with a significant morbidity. Usually, clinical manifestations, laboratory findings, and imaging are used to differentiate between lower and upper UTI. Lack of specific clinical findings and commonly used nonspecific blood indices are important hamper differentiation between lower and upper UTI in early stages. Imaging techniques are neither cost benefit nor safe for detection of UTI. Recent efforts have focused on characterization of novel serum and urinary biomarkers for early detection of acute pyelonephritis in children. It seems that urinary NGAL, NAG, TNF-α and IL-8 may be used as novel markers for early diagnosis of acute pyelonephritis in children.